2021
DOI: 10.1186/s12905-021-01272-x
|View full text |Cite
|
Sign up to set email alerts
|

Iranian women’s psychological responses to positive HPV test result: a qualitative study

Abstract: Background Human papillomavirus testing as an established screenings test allow for the early detection and treatment of cervical cancer. Testing positive for HPV may have adverse consequences for women. This study aimed to explore the psychological impacts of testing positive for HPV on women in a developing country with a distinct cultural and religious background. Methods Qualitative face-to-face semi-structured interviews were conducted with 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A body of research showed that GWs can change the appearance of the vulva, causing embarrassment and anxiety and the quality of sexual relationships [ 10 ]. As there is no HPV vaccination yet in Iran, and sexual relationships are only acceptable for married women in the culture, the sexually transmitted infection test is quite a challenge for most women [ 19 ]. It seems that preventing infection is the best strategy in this region.…”
Section: Introductionmentioning
confidence: 99%
“…A body of research showed that GWs can change the appearance of the vulva, causing embarrassment and anxiety and the quality of sexual relationships [ 10 ]. As there is no HPV vaccination yet in Iran, and sexual relationships are only acceptable for married women in the culture, the sexually transmitted infection test is quite a challenge for most women [ 19 ]. It seems that preventing infection is the best strategy in this region.…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature shows that the studies conducted on HPV are mostly focused on women, and such matters as quality of life [ 10 ], marital adaptation to the infection (using a quantitative approach) [ 11 ], vaccination [ 12 ], the psycho-sexual effects of being diagnosed with HPV [ 13 , 14 ], women’s experiences of facing their infection [ 15 ], women’s psychological responses to positive HPV test [ 16 ], the information management processes of women living with HPV [ 17 ], and reproductive concerns of HPV- positive women [ 18 ]. Research findings show that testing positive for human papillomavirus is accompanied by feelings of shame, stigma, self-deprecation, regret, anxiety and concern [ 16 , 18 , 19 ]. To the best knowledge of the authors, no work of research has addressed the process of adaptation in men and women with HPV.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this finding is unknown; it may be difficult to draw any real conclusions from this finding given the small number participants who self-reported being “HPV-positive”. However, women may assume that being “HPV-positive” means they would definitely develop cervical cancer in the future [ 50 ] and thus not perceive the preventive benefit of adhering to screening recommendations.…”
Section: Discussionmentioning
confidence: 99%